Estruturas narrativas da hipermídia: uso e interações contemporâneas - Melo, Antonio Carlos de (2008)
The aim of this research is to talk about the narrative structures in different stages and historical contexts. According to the investigation line, I intend to do relations between the narratives from the XV century on, here represented by the origin of the printed culture, and the use and contemporary interactions in the hypermedia. The use and contemporary interactions are the constant technological updating and the resultant evolution of the creation processes. The narrative in the digital universe, the influential innovations and the potential in immersive, participative, encyclopedic and space environments lead us to a reflection of the imaginary, to the pleasures that this cyberliterature will bring to the narrative art and the promise of a new way of expression, like the printed books and the cinema, finally the future of the narrative in the digital environment. The hybrid of languages and ways, before the new technologies of intelligence change the format of the narratives structures in the support of the hypermedia inside the context of cyberspace